Replication process of the parvovirus H-1. VI. Characterization of a replication terminus of H-1 replicative-form DNA. - Rhode, S L (1977)
The linear duplex replicative form (RF) DNA of the parvovirus H-1 has been characterized with respect to cleavage by the bacterial restriction endonuclease of Escherichia coli, EcoRI. RF DNA has a single cleavage site 0.22 genome length from the left end of the molecule. The molecular weight of H-1 RF DNA determined by gel electrophoresis is 3.26 X 10(6). H-1 RF DNA has been found to dimerize by hydrogen-bounded linkage at the molecular left end, and in some molecules the viral strand is covalently linked to the complementary strand. Some 10% of monomeric RF DNA also has a covalent linkage between the viral and complementary strands at the left end. The EcoRI-B fragment, containing the left end of the RF molecule, appears to be a replication terminus by its labeling characteristics for both RF and progeny DNA synthesis. These findings suggest that the left end of H-1 RF DNA has some type of "turn-around" structure and that this end is not an origin for DNA synthesis.